PENGARUH MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBASIS AJARAN TRI KAYA PARISUDHA TERHADAP MINAT BELAJAR PENDIDIKAN AGAMA HINDU SISWA KELAS XI SMK NEGERI 2 SINGARAJA - Deviantari, Desak Made Della; Darma, I Wayan Wira; Tristananda, Putu Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to find out how different learning methods influence students' interest in learning. This study uses a quantitative approach and follows a quasi-experimental design, specifically a post-test only with a control group. The population in this study consisted of 403 students, and the sampling method used was cluster random sampling. The experimental group was class XI TK3, which had 33 students, and the control group was class XI K7, which had 39 students. The study used questionnaires, document reviews, and testing methods to check if the tools were valid and reliable. The data analysis methods that were used included checking for normality, ensuring homogeneity, and conducting hypothesis tests. Data examination employing independent sample test revealed that Sig. (2-tailed) 0.000 <0.05 means Ha is accepted and H0 is rejected. So there is a significant difference in the influence of the Teams Games Tournament learning model based on the teachings of Tri Kaya Parisudha on the Interest in Learning Hindu Religious Education of Class XI Students of SMK Negeri 2 Singaraja.